Diseño y desarrollo de mobiliario multifuncional en el ámbito del estudio y el juego enfocado en la simulación de carreras (2021)
Desk is a project that consists of a furniture-type product, which is a multifunctional workstation focused on offering a bridge that unites in one single product in function and aesthetics, the ecosystem of study/work and the /work and the Gamer of the racing simulation sector. This project will see the convergence of 2 areas, the Work Station and the Game Station, both of which are well known in the market, where the ergonomic, structural and aesthetic aspects will be influenced in order to maintain a dual structural and aesthetic aspects will be influenced to maintain an inverse duality duality for each mode in the same product.